Cosmopolitanism with Room for Nationalism - Lee, Win-Chiat (Journal of moral philosophy, 2012)
Gillian Brock attempts to reconcile cosmopolitanism with nationalism in Global Justice: A Cosmopolitan Account. She claims that her cosmopolitanism leaves room for legitimate nationalism. I argue that her cosmopolitanism is not only a theory of global justice, but also a general theory of justice, according to which what justice may demand of us is fundamentally global in nature. As such, Brock’s cosmopolitanism cannot accommodate nationalism in the overall structure of what justice may demand of us, but has to relegate it to the discretionary space left open after what justice may demand of us globally has been met. This does not amount to much of a reconciliation or a particularly moderate cosmopolitanism, contrary to Brock’s claim. More important, I argue, Brock’s cosmopolitan theory of justice need not follow from the more fundamental view of moral cosmopolitanism.